Strategi Mengatasi Kesepian pada Pria Dewasa Awal Penyandang Tunanetra - Swestilangen, Rasti Sindu; Syafiq, Muhammad (Utan Kayu Publishing, 2021)
Visually impaired person has obstacles in terms of limited mobility orientation causing problems in interpersonal relationships. These interpersonal problems can lead to discomfort and feelings of loneliness. This study aims to explore the experience of visually impaired men in young adulthood related to loneliness and how they cope with it. A qualitative method with a phenomenological approach was employed. Six visually impaired men in early adulthood were recruited as research subjects using purposive and snowball sampling techniques. Data were collected using semi-structured interviews and analyzed using an interpretative phenomenological analysis. The results showed that all subjects reported that they experience emotional and social loneliness due to their visual impairment condition. The feelings of loneliness they experienced cannot be separated from their sense of self-worthlessness and the perceived negative social responses they faced from surrounding people. Both personal and social obstacles have reduced the quality of their social relationship which eventually impact on their feeling of loneliness. In general, the subjects have efficaciously effort to overcome their loneliness by using cognitive reevaluation, doing leisure activities as consolation and taking active actions to improve social relations. Penyandang tunanetra memiliki keterbatasan dalam orientasi mobilitas yang menyebabkan permasalahan dalam hubungan interpersonal. Permasalahan hubungan interpersonal ini dapat mengakibatkan kesepian. Penelitian ini bertujuan untuk mengeksplorasi pengalaman pria dewasa awal penyandang tunanetra terkait kesepian dan bagaimana strategi mereka dalam mengatasinya. Penelitian kualitatif dengan metode fenomenologi digunakan. Enam pria dewasa awal penyandang tunanetra berhasil direkrut menggunakan teknik purposif dan snowball. Data dikumpulkan melalui wawancara semiterstruktur dan dianalisis menggunakan interpretative phenomenological analysis. Hasil penelitian menunjukkan bahwa semua subjek mengalami kesepian akibat dari kondisi gangguan penglihatannya. Rasa rendah diri dan persepsi atas munculnya respon negatif dari orang sekitar menjadi penghalang hubungan sosial mereka, yang pada akhirnya berdampak pada kesepian. Secara umum, para subjek berusaha mengatasi kesepian dengan melakukan reevaluasi kognitif atas keterbatasan mereka dan respon orang, melakukan aktivitas sebagai pengalihan, dan aktif bertindak adaptif untuk meningkatkan kualitas hubungan sosial.